Budaya Penjara: Arena Sosial Semi Otonom di Lembaga Pemasyarakatan “X” - Josias Simon Runturambi (Antropologi Indonesia, 2013)
This paper is an ethnographic study to understand the prison’s culture in the correctional institutions “X”. The writer has examined carefully the way of living day by day directly and raised a variety of mutual agreements among the residents behind the prison walls. The results in the investigation field shows the limit and deprivation that appears as an interpretation actor, not the institution, that occur according certain contexts. The prison’s culture not only discuss informal agreement but how the agreements can be maintained by the actors in everyday’s life utilization in fulfilling the needs and self-interestsKeyword: Prison’s Culture, Correctional Institution, Semi Autonomous Social Fields, Actor, Context